Simulação numérica da influência da carga excêntrica e da altura do embutimento da estaca no comportamento estrutural de blocos rígidos de concreto armado sobre duas estacas - Rocha, Cleyton Éder Rodrigues Rocha (2024)
Deep foundations, such as piles and caissons, are responsible for supporting buildings and rely on cap blocks to distribute loads to the soil. Therefore, correct block design and execution are essential processes to ensure the safety and efficiency of constructions. Upon reviewing the literature, it was noticed that two factors can affect the proper performance of blocks. The first is the application of eccentric load, which can impact stress distribution and the load-bearing capacity of blocks on piles. The second is inadequate embedding of piles in blocks, which can also lead to possible structural failures. Consequently, there was a need to understand the structural behavior of the block under these factors, identifying critical points in the system and thus contributing to a more suitable design. The objective of this work was to analyze the influence of pile embedment height in the block and the eccentricity of loads applied to the rectangular section pillar in a block over two square-section piles, through non-linear numerical simulation using the finite element method in the ABAQUS® software. Equal and different embedment heights were adopted for the two piles, with values of 5 cm, 10 cm, and 15 cm. Eccentric load was applied, which could be to the left or right of the pillar axis, at 0 cm, 5 cm, 10 cm, and 15 cm, totaling 33 models. The results were compared with a reference model calibrated in this work. As a result, it was observed that models with eccentricities showed less resistance, exhibiting losses of up to 30% of strength compared to centrally loaded ones. The variation in pile embedment had little influence on final strength, but models with 15 cm embedments of piles showed more resistance due to higher stress in the tie reinforcement, especially under centrally loaded conditions. Models with varied pile embedment showed lower ultimate resistance when the vertical displacement applied to the pillar was in the direction of the less embedded pile. Finally, early concrete damage was more evident in models with greater embedment, highlighting its importance in damage propagation. For shallower pile embedments, initial damage appeared at around 20% of the ultimate force, while deeper embedments experienced initial damage at around 15% of this force.